2013
DOI: 10.1002/dta.1581
|View full text |Cite
|
Sign up to set email alerts
|

THCCOOH concentrations in whole blood: Are they useful in discriminating occasional from heavy smokers?

Abstract: Some forensic and clinical circumstances require knowledge of the frequency of drug use. Care of the patient, administrative, and legal consequences will be different if the subject is a regular or an occasional cannabis smoker. To this end, 11-nor-9-carboxy-Δ9-tetrahydrocannabinol (THCCOOH) has been proposed as a criterion to help to distinguish between these two groups of users. However, to date this indicator has not been adequately assessed under experimental conditions. We carried out a controlled adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 19 publications
1
29
1
Order By: Relevance
“…Further details regarding the inclusion procedure are indicated in Battistella et al (2013). In both groups of cannabis users, we performed a urine and a blood test during the inclusion process in order to determine the concentration of Δ9-Tetrahydrocannabinol-carboxylic acid (THCCOOH) and confirm the regular use and the extent of cannabis consumption (Fabritius et al , 2013b). Participants also filled out a questionnaire about their usual drug use habits.…”
Section: Methodsmentioning
confidence: 99%
“…Further details regarding the inclusion procedure are indicated in Battistella et al (2013). In both groups of cannabis users, we performed a urine and a blood test during the inclusion process in order to determine the concentration of Δ9-Tetrahydrocannabinol-carboxylic acid (THCCOOH) and confirm the regular use and the extent of cannabis consumption (Fabritius et al , 2013b). Participants also filled out a questionnaire about their usual drug use habits.…”
Section: Methodsmentioning
confidence: 99%
“…After a proven period of abstinence and regular medical checkups, the driver's license may be re-issued. In the study conducted by Fabritius et al [17] the 40 µg/L cut-off for free THCCOOH showed a low sensitivity, implying that its ability to correctly identify heavy users is rather poor. Since THCCOOH in blood is extensively glucuronidated [19], we hypothesize that the free THCCOOH blood level is not solely determined by the consumption frequency, but is also dependent on the individual glucuronidation rate.…”
Section: Introductionmentioning
confidence: 94%
“…Further biotransformation via phase II glucuronidation produces hydrophilic conjugates that are easily excreted [11]. Due to its long elimination half-life [11] , THCCOOH accumulates in the blood upon regular cannabis use [12][13][14][15] and has therefore been proposed as diagnostic marker to distinguish between occasional and heavy users [16,17]. In Switzerland, a free THCCOOH blood level of 40 µg/L is currently used as cut-off for the classification of impaired drivers as heavy users, as recommended by Fabritius et al [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fabritius et al [48] in this issue recommend a way forward, based on the combination of findings from analysis of whole blood THC and a medical interview of the driver, in the context of the zero tolerance policy in their country, Switzerland. This is not a trivial consideration and can have cost implications for governments that consider it important to have follow-up investigations of offending drivers to answer this question.…”
Section: Cannabis and Drivingmentioning
confidence: 99%